Assessing the pedestrian response to urban outdoor lighting: A full-scale laboratory study - Rahm, Johan; Johansson, Maria (Faculty of engineering, Lund University, 2018)
The study employed a mixed design, with a within subjects repeated measures design for evaluating differences due to the different lighting applications, and a between groups design for exploring differences due to age. Each participant performed the test procedure three times, once for each lighting application. The luminaires were shifted by rotating the top of the lamppost and the presentation order was counterbalanced.


More information is available in published article https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0204638

Purpose:

The study aims to identify and explore methods for evaluating the human response to pedestrian lighting applications.

Studien följde en mix-design; inom-individdesign för att utvärdera skillnader mellan belysningslösningarna och mellan-individdesign för att utforska åldersskillnader. Varje deltagare utförde momenten tre gånger, en gång för varje belysningslösning. Ljuskällorna byttes ut genom att toppen på lyktstolpen roterades. Presentationsordningen var balanserad.


Mer information finns att ta del av via publicerad artikel https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0204638

Syfte:

Studien syftar till att identifiera och utforska metoder som kan användas för att utvärdera fotgängares ljusupplevelser.
Undersökning av fotgängares upplevelse av utomhusbelysning: En laboratoriestudie
Keywords: lighting; belysning; electric lighting; elektrisk belysning; PSYCHOLOGY; PSYKOLOGI; Social Sciences; Samhällsvetenskap; Psychology; Psykologi; Applied Psychology; Tillämpad psykologi